2014
DOI: 10.1038/cddis.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 mediates the impairment of ubiquitin-proteasome and autophagy-lysosome pathways induced by ethanol treatment in brain

Abstract: New evidence indicates the involvement of protein degradation dysfunctions in neurodegeneration, innate immunity response and alcohol hepatotoxicity. We recently demonstrated that ethanol increases brain proinflammatory mediators and causes brain damage by activating Toll-like receptor 4 (TLR4) signaling in glia. However, it is uncertain if the ubiquitin-proteasome and autophagy-lysosome pathways are involved in ethanol-induced brain damage and whether the TLR4 response is implicated in proteolytic processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 59 publications
0
56
0
Order By: Relevance
“…48 Intriguingly, autophagy has also been implicated to play a neuroprotective role in the context of alcohol 49 and is shown to involve TLR-mediated pathways. 50 Additionally, cannabinoids also induce autophagy in human glioma cells. 29 Our findings for the first time suggest that yet another drug, cocaine can induce autophagy in microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…48 Intriguingly, autophagy has also been implicated to play a neuroprotective role in the context of alcohol 49 and is shown to involve TLR-mediated pathways. 50 Additionally, cannabinoids also induce autophagy in human glioma cells. 29 Our findings for the first time suggest that yet another drug, cocaine can induce autophagy in microglial cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, chronic ethanol exposure in adult mice activates MTOR and causes impairment of the autophagy-lysosome pathway in the brain. 46 This implies that long-term exposure to ethanol may damage this protective system and further jeopardize CNS neurons to subsequent ethanol exposure and other insults. In turn, this finding suggests that upregulation of autophagy may be beneficial not only for the damage caused by acute ethanol exposure in the developing brain but also for deficits in the adult brain induced by chronic exposure.…”
Section: Autophagic Protection Against Ethanol-mediated Neuronal Damagementioning
confidence: 99%
“…46 The mechanisms of ethanol inhibition of MTORC1 are unclear. Ethanol induces ROS production and affects several upstream kinases of MTORC1, such as PI3K-AKT and GSK3B in neurons.…”
mentioning
confidence: 99%
“…This CBA-specific up-regulation is potentially due to increased immunoproteasome activity. Supporting this interpretation, chronic alcohol administration increases the expression of immunoproteasome subunits and catalytic activity in brain tissue [28]. Furthermore, using this same model of CBA and SIV infection, we previously reported that proteasome subunit expression is dysregulated and proteasome activity is increased in skeletal muscle of CBA/SIV+ macaques [11].…”
Section: Discussionmentioning
confidence: 69%